2019
DOI: 10.9740/mhc.2019.05.110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of a social media–focused intervention on reducing mental health stigma among pharmacy students

Abstract: Introduction Stigma may negatively affect the treatment of people with mental illness, and pharmacists have the opportunity to play a key role in reducing mental health stigma. The purpose of this study was to determine whether a pharmacy student–focused educational intervention impacts stigma toward people with mental illness. Methods A 90-minute interactive learning module, which used social media and fictional case scenari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…When compared to other populations in previous studies that adopted the 15-item OMS-HC, the results indicate a relatively high stigmatizing behavior among the study subjects. For instance, in the work of Douglass and Moy (2019) evaluating the impact of a social media-focused intervention on mental health stigma among a university sample of pharmacy students in the United States, both pre-and post-intervention scores (36.8 and 35.1, respectively) are markedly lower compared to the current results [30]. Among working pharmacists in Accra, the overall score was 37, which is also significantly lower in comparison to the current findings [31].…”
Section: Discussioncontrasting
confidence: 71%
“…When compared to other populations in previous studies that adopted the 15-item OMS-HC, the results indicate a relatively high stigmatizing behavior among the study subjects. For instance, in the work of Douglass and Moy (2019) evaluating the impact of a social media-focused intervention on mental health stigma among a university sample of pharmacy students in the United States, both pre-and post-intervention scores (36.8 and 35.1, respectively) are markedly lower compared to the current results [30]. Among working pharmacists in Accra, the overall score was 37, which is also significantly lower in comparison to the current findings [31].…”
Section: Discussioncontrasting
confidence: 71%
“…On the other hand, it is reasonable to think that some individuals who are experiencing depression and anxiety may be more likely to engage with social media, possibly as a method of support. Social media can have some beneficial purposes ( 60 ), including reducing stigma around mental health ( 61 ). In the context of the current COVID-19 pandemic, more research will be needed to determine whether different reasons for use of social media are predictive of different mental health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Douglass et.al, 2019 reported that stigma has a significant impact on the treatment of MH, with substantial implications on patient quality of life. To provide professional, culturally sensitive care, pharmacists should reflect on their skills, attitudes, and beliefs of MH treatment and actively participate in changing the stigma of mental illnesses [47]. Evidence suggests that socioeconomic factors can have the greatest effect on health and wellbeing, accounting for 40% of all influences on the individual.…”
Section: Fig-1: Changing the Conversation About Mental Health (Mh) [1]mentioning
confidence: 99%